Informed consent in dental practice among dental professionals in Karnataka - K., Vanishree M.; Panchmal, Ganesh Shenoy; K., Umashankar G. (International Journal Of Community Medicine And Public Health, 2021)
Background: The purpose of informed consent is to assure that the patient has a full understanding of proposed treatment and can make a relevant health-care decision based on the information provided by the health-care professional. Many health-care professionals see the process as burdensome and time-consuming. It is also one of the common allegations in many professional liabilities claims against health professionals. Informed consent focuses on patients’ absolute right to understand their status and the practitioner’s proposed treatment plan. Informed consent is the educational process by which the patient is made aware of the dentist’s diagnosis and treatment plan. Studies have shown that 40% of the written consent obtained from the parents was not valid. Making an informed decision is the right of every patient, but it is the responsibility of dentists to ensure patients have the comprehensive information needed to exercise that right. Methods: A cross-sectional study was done to assess the knowledge, attitude and practice of informed consent among 865 dental professionals practicing in Karnataka. The study used the validated structured questionnaire. Results: The results showed 94.8% of the participants agreed that the key step to prevent one’s practice from legal action is valid informed consent. The mean scores were used for analysis the total knowledge, attitude and practice scores for the participants were 19.01±2.61, 7.07±1.45 and 1.49±0.50 respectively. Only 37.3% of dental professionals took written informed consent and majority i.e., 54.5% took consent only for special cases. Conclusions: Though the dentist believed in taking informed consent. Consent in practice is not taken routinely.